Mangrove Forest Tourism Development Strategy: A Study Case of Nai Nang Village Thailand - worrapot treesuk; Aldi Wisnumurti Sarwono; Weavy Kherenhapukh; Annisa Rachma (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Abstract: Nai Nang Village Mangrove Forest is one of the tourist attractions in Krabi Thailand. The destination of this mangrove forest area is very wide and has a variety of trees with a considerable number, especially mangrove trees and even some species of animals present in it. In addition, in this mangrove forest has a beekeeping farm where honey can be processed as a typical souvenir and used as an educational tour of beekeeping. But at the time the author conducted this mangrove forest research in a quiet situation and not widely known by foreign tourists. Mangrove forest is also not managed to the maximum. Purpose: This research aims to answer how tourism development strategies can be done so as to reduce the number of tourist visits and answer how the role of the community to the development of Nai Nang Village Mangrove Forest. Research methods: The research method used is Qualitative Research. Data collection techniques by means of observation, interview, and documentation. Then the data is analyzed using SWOT analysis. Results and discussions: The results of this study the manager needs to improve the quality of cleanliness, promotion, exploring the potential of tourism either from the cultural, social, natural or community elements itself so as not to lose to other competitors. As well as taking care of mangrove forest regulation in order to get full support from the local government that will have a big impact on tourism development in Nai Nang Mangrove Debt. Conclusion: The role of the community in the development of mangrove forests is quite large from participating in the organization of management, group workshops with the manufacture of value-added products such as hand soap, shampoo, and conditioner with honey as souvenirs typical of the local area where as a promotional media. The local community also accompanies and mentors people who want to do bee education tours